Ingestive behavior of lambs or hoggets fed on high-concentrate diets of maize or sorghum - Venturini, Rafael; Carvalho, Sérgio; Teixeira, Camilla; de Pellegrini, Luiz Gustavo; Brutti, Danielle (Revista Ciência Agronômica, 2017)
The aim of this study was to evaluate the ingestive behaviour of lambs or hoggets, finished in confinement on high-concentrate diets based on maize or sorghum grain. A total of 32 animals were used, 16 lambs (milk teeth) and 16 hoggets (2 teeth), which were distributed in a completely randomised experimental design and a 2 x 2 factorial scheme (two categories x two types of grain). In the categories under evaluation (lambs and hoggets), a significant difference (P≤0.05) was found for total chewing time, idle time and other activities (expressed in min/day and as a percentage), number of meals per day, time spent per meal and for the weight of dry matter or NDF ingested per meal (g/DM per REF and g/NDF per REF respectively). For the grain under test (maize or sorghum), significant differences (P≤0.05) were seen in feeding time, total chewing time and idle time (expressed in min/day and as a percentage) and for feed efficiency (g DM/h and NDF/h). Differences in the nutritional demands of lambs and hoggets, and in the composition of high-concentrate diets of maize or sorghum, cause changes in some characteristics of the ingestive behaviour of the animals.